PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Putra, Putu Didit Pramana; Sriathi, A.A. Ayu (E-Jurnal Manajemen, 2017)
Organizational citizenhip behavior is an in-depth contribution by employees where employees are willing to work voluntarily outside of their work. The main problem in this research is there are employees who are reluctant to help their colleagues, employees are reluctant to replace colleagues who do not work, employees do not work, employee complaints about the job, and disinterest employees to the company's activities. The number of samples taken is 74 employees, with simple random sampling method. Based on the results of multiple linear regression analysis indicates perceived organizational support and organizational commitment have a positive and significant effect on Organizational citizenhip behaviour. Organizational citizenhip behavior can increase if affected by both variables.